Latent profile analysis of psychological abuse and neglect and the relationship with depression and anxiety: a multicentre cross-sectional study in western Chinese adolescents - Yu Cen; Jiarui Shao; Cailin Xie; Ping Mo; Xingyu He; Jiaming Luo (European Journal of Psychotraumatology)
Background: While many studies link psychological abuse and neglect to mental health issues in adolescents, they often overlook the internal heterogeneity of these factors. This study aims to explore the characteristics of psychological abuse and neglect among adolescents in Western China and examine their relationship with depression and anxiety, providing insights for targeted interventions.Methods: A survey was conducted on 18,350 students in Western China using the Child Psychological Abuse and Neglect Scale (CPANS), the Patient Health Questionnaire Depression Scale (PHQ-9), and the Generalized Anxiety Disorder Scale (GAD-7). Latent profile analysis was used to classify the characteristics of adolescent psychological abuse and neglect. Chi-square tests and variance analysis were employed to explore demographic differences among different characteristic groups. Additionally, the BCH method was used to compare whether differences in depression and anxiety existed across each profile.Results: Latent profile analysis revealed three categories for psychological abuse (‘no abuse,’ ‘at risk,’ ‘abuse’) and neglect (‘no neglect,’ ‘at risk,’ ‘neglect’). Older adolescents, females, those experiencing parental absence, and those from broken homes were more likely to be in the ‘abuse’/‘neglect’ categories. Adolescents in these groups had higher levels of depression and anxiety compared to those in the ‘at risk’ groups. Additionally, those in the ‘at risk’ groups exhibited higher levels of depression and anxiety than those in the ‘no abuse’/‘no neglect’ categories.Conclusion: The characteristics of psychological abuse and neglect can predict depression and anxiety levels. These findings highlight the value of latent profile analysis in understanding the complex relationship between psychological abuse, neglect, and mental health issues in adolescents.